Thermo-swing insulation to reduce heat loss from the combustion chamber wall of a diesel engine. (September 2019) - Kawaguchi, Akio; Wakisaka, Yoshifumi; Nishikawa, Naoki; Kosaka, Hidemasa; Yamashita, Hideo; Yamashita, Chikanori; Iguma, Hiroki; Fukui, Kenji; Takada, Noriyuki; Tomoda, Terutoshi
Cooling heat loss is one of the most dominant losses among the various engine losses to be reduced. Although many attempts to reduce it by insulating the combustion chamber wall have been carried out, most of them have not been successful. Charge air heating by the constantly high temperature insulating wall is a significant issue, because it deteriorates charging efficiency, increases the emissions of soot and NOx in diesel engines, and promotes the knock occurrence tendency in gasoline engines. A new concept heat insulation methodology which can reduce cooling heat loss without heating the charging air has been developed. Surface temperature of insulation coating on the combustion chamber wall changes rapidly, according to the quickly changing in-cylinder gas temperature in each engine stroke. During the compression and expansion stroke, the surface temperature of the insulation coating goes up rapidly, and consequently, the heat transfer becomes lower by the reduced temperature difference between the surface and the gas. During the intake stroke, the surface temperature goes down rapidly, and it prevents intake air heating from the wall. To realize the above-mentioned functionality, a thin coating layer with low thermal conductivity and low heat capacity was developed. It was applied on the pistons of diesel engines, and showed improvement in thermal efficiency. It also showed a reduction of unburnt fuel emission in low temperature engine starting condition. The energy balance analysis showed reduction of cooling heat loss and, on the contrary, increase in the brake power and the exhaust loss.